Development of an Augmented Reality Smart Book on the Solar System to Improve Science Literacy of Elementary School Students - Nisa, Rofiatun; Abdillah, Khumaidi; Priyanto, Randi; Tsuroiyah, Afro (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
This study aims to develop and test the validity, practicality, and effectiveness of AR-based Smart Books in improving students' scientific literacy. The method used is the Plomp model research and development (R&D), including the preliminary research stage, prototyping, and assessment. The trial involved 252 sixth-grade students from 14 Islamic Elementary Schools in Lamongan Regency (126 experimental classes, 126 control classes). Data collection techniques used a validation questionnaire by language experts, material, and media questionnaires on product appeal to students; pretest and posttest questionnaires; observation sheets; and interviews. Data analysis used prerequisite tests including normality tests with Kolmogorov-Smirnov and homogeneity of variance tests with Levene; effectiveness tests using ANCOVA and N-Gain processed through IBM SPSS Statistics version 21. The validation results by media experts obtained an average of 4.75, material experts obtained an average of 4.67, and language experts obtained an average of 4.73 which indicates a very valid category. The practicality test showed 94% implementation and 93.85% product attractiveness (very attractive). The ANCOVA results showed a significant effect on scientific literacy, F(1,249) = 38.689, p < 0.001, with a large effect size (η² = 0.134). The N-Gain score of the experimental group (0.85) was higher than the control group (0.65). It can be concluded that the AR Smart Book of the Solar System is valid, practical, and effective to be used as an innovative learning medium to improve the scientific literacy of Madrasah Ibtidaiyah students